Cecilia Cuțescu – Storck (1879 – 1969) (Confluenţe Bibliologice, 2019)
The postage stamp issue “Cecilia Cutescu-Storck 140th anniversary of her birth”, which Romﬁlatelia  introduced into circulation on  March 14th, 2019  is dedicated to the celebration of the life and personality of the ﬁrst female professor of decorative arts in Romania, also noted as the ﬁrst female teacher at a State Art University in Europe. She  left a remarkable artistic heritage.
Keywords: Cecilia Cuțescu – Storck (1879 – 1969); postage stamps; romanian art